A Phenomenological Study of School Heads' Lived Experiences Between Teaching-Learning and School Administration - Jhonie D. Gumilao; Liezl Marie B. Dagondon (CV. Literasi Indonesia, 2026)
This hermeneutic phenomenological study delved into the lived experiences of school heads in the Department of Education, Region IX, Philippines, as they navigated the dual imperatives of instructional leadership and school administration. Framed by the MATATAG Agenda and the Philippine Professional Standards for School Heads (PPSSH), this research addressed a gap in understanding the personal, emotional, and meaning-making aspects of educational leadership in the Philippine context, using a hermeneutic-phenomenological research design. Through in-depth interviews with 7 school heads from DepEd Region IX, the study uncovered the essence of their leadership as a dynamic, often tense, process of orchestrating harmony. Three constitutive themes emerged: (1) The Duality of Role and Identity: A Constant Tug-of-War; (2) The Moral Compass: Navigating Pressures Through Foundational Values; and (3) The Hermeneutics of Policy: Translating Abstract Directives into Lived Reality. The findings revealed that effective leadership transcended mere compliance with standards; it was an interpretive, value-laden practice that created coherence and fostered growth in the face of systemic challenges. Recommendations were offered for refining policy, developing leadership development programs, and conducting future research.